BRAFV600E mutant protein is expressed in cells of variable maturation in Langerhans cell histiocytosis - Sahm, Felix; Capper, David; Preusser, Matthias; Meyer, Jochen; Stenzinger, Albrecht; Lasitschka, Felix; Bergmeister-Berghoff, Anna Sophie; Habel, Antje; Kulozik, Andreas; Anagnostopoulos, Ioannis; Mechtersheimer, Gunhild; Deimling, Andreas von (Blood, 2012)
Langerhans cell histiocytosis (LCH) is a clinically and histologically heterogeneous disorder. Its classification as either reactive inflammatory or neoplastic has been a matter of debate. However, the recent finding of frequent BRAFV600E mutations in LCH argues for the latter. The exact cell type that harbors the mutation and is responsible for proliferation remains to be identified. We here apply a BRAFV600E mutation-specific antibody to detect the BRAF mutant cells in lesions from 89 patients with LCH. We found BRAFV600E mutations in 34 of 89 (38%) lesions. In lesions with the BRAFV600E mutation, the majority of cells coexpressing S-100 and CD1a harbored mutant BRAFV600E protein. These cells also expressed CD14 and CD36, whereas various fractions exhibited CD207. On the other hand, CD80 and CD86 expression was also present on BRAFV600E-positive cells. Thus, cells of variable maturation, exhibiting an immunohistochemical profile compatible either with myeloid cell or with dedifferentiated Langerhans cell antigens, carry the BRAFV600E mutation. In conclusion, we identify and characterize the neoplastic cells in LCH with BRAFV600E mutations by applying a mutation-specific marker and demonstrate feasibility for routine screening.
Published online September 20, 2012
Gesehen am 13.06.2018